Prevalence of rotavirus infection and its association with socio-demographic characteristics among under-five children admitted with acute diarrhoea in a tertiary care hospital of Bangladesh - Habib, Farjana Binte; Rahman, Mohammed Mirazur; Choudhury, Rafaat; Paul, Tarun Kanti; Haque, Md Moynul (BIRDEM Medical Journal, 2021)
Background: Rotavirus has been recognized as the most common cause of acute watery diarrhoea among under-five children worldwide. It is considered as a major cause of childhood morbidity and mortality particularly in developing countries like Bangladesh. Considering the high morbidity and significant mortality, this study was designed to evaluate the prevalence of rotaviral diarrhoea among children less than five years in Sylhet region of Bangladesh. Methods: This cross-sectional study was conducted in the Department of Microbiology, Sylhet MAG Osmani Medical College from 1st January to 31st December, 2018. Total 184 under-five children admitted in paediatrics department of the same institute with acute watery diarrhoea were enrolled in this study by convenient sampling. Stool samples were obtained and assayed for rotavirus antigen by sandwich type enzyme linked immunosorbent assay (ELISA). Results: Rotaviral antigen was found positive in 86 cases and disease prevalence was 46.74%. The rotavirus infection was found highest in age group of 7 to 12 months (50.56%) and in male (59.30%) children. Prevalence of infection was associated with age (p= 0.004), socio-economic condition (p=0.001) and exclusive breastfeeding of children (p=0.01). Conclusion: Rotavirus was a significant cause of acute watery diarrhoea and mainly affected children below 12 months age. BIRDEM Med J 2021; 11(3): 186-190